2008
DOI: 10.1021/ja803332h
|View full text |Cite
|
Sign up to set email alerts
|

Alkene Hydrosilation by a Cationic Hydrogen-Substituted Iridium Silylene Complex

Abstract: A cationic hydrogen-substituted iridium silylene complex [(PNP)(H)Ir Si(Mes)H][B(C6F5)4] (2) was synthesized via hydride abstraction from the corresponding neutral iridium silyl hydride complex. DFT calculations for 2 indicate that the cationic charge is localized at the silicon center and depict a LUMO with predominant silicon p-orbital character. Notably, complex 2 reacts rapidly with unhindered alkenes at ambient temperatures to afford disubstituted silylene complexes via Si-C bond formation. Complex 2 is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
63
0
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 18 publications
1
63
0
10
Order By: Relevance
“…More recently, this reaction type has been extended to iridium. [76] Finally, the iridium silylene complex [Cp*A C H T U N G T R E N N U N G (PMe 3 ) 2 Ir- 4 ] was found to catalyze the hydrosilylation of ketones, even though the involvement of a metalmediated or of a Lewis acid mechanism could not be clearly distinguished. [77] Comparison of the three mechanistic pathways: The energetics of the three computationally established catalytic cycles have been depicted in Figures 6, 8, and 10, in the preceding sections.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, this reaction type has been extended to iridium. [76] Finally, the iridium silylene complex [Cp*A C H T U N G T R E N N U N G (PMe 3 ) 2 Ir- 4 ] was found to catalyze the hydrosilylation of ketones, even though the involvement of a metalmediated or of a Lewis acid mechanism could not be clearly distinguished. [77] Comparison of the three mechanistic pathways: The energetics of the three computationally established catalytic cycles have been depicted in Figures 6, 8, and 10, in the preceding sections.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to ruthenium, Tilley and coworkers also reported that cationic iridium silylenoid complexes were efficient olefin hydrosilation catalysts [reaction (7.6)]. 56 This silylene complex catalyzes the hydrosilation of unhindered mono-or disubstituted olefins with primary silanes to produce secondary silanes with anti Markovnikov selectivity. Iridium catalyst 32 exhibited reactivity patterns similar to those of ruthenium 30; only primary silanes were allowed as substrates.…”
Section: Transition Metal Silylenoid Complex-catalyzed Hydrosilation mentioning
confidence: 99%
“…[15] This system is a relatively poor s donor but a good p donor and readily forms well-defined rhodium, iridium, and other metal complexes that exhibit interesting reactivity, coordination chemistry, and catalytic activity with a variety of substrates. [15][16][17][18][19][20][21][22][23][24] For example, complex 1 is also successful in activating various substrates by C À H and aryl-halide oxidative addition, [14,25,26] regioselective alkyne dimerization, and Heck olefin arylation. [15] Calimano and Tilley very recently used this popular complex (1) to generate an iridium-silylene complex that efficiently catalyzes the anti-Markovnikov hydrosilylation of alkenes by direct addition of the silicon-hydrogen bond of both aryl and alkyl-substituted primary silanes to carboncarbon double bonds.…”
mentioning
confidence: 99%
“…[15] Calimano and Tilley very recently used this popular complex (1) to generate an iridium-silylene complex that efficiently catalyzes the anti-Markovnikov hydrosilylation of alkenes by direct addition of the silicon-hydrogen bond of both aryl and alkyl-substituted primary silanes to carboncarbon double bonds. [26] The mechanism underlying the remarkable carbon dioxide reduction coupled with oxygen atom transfer to a Fischer carbene has been elucidated in much detail by Whited and Grubbs (Scheme 2). [9,27] The reaction pathway includes some interesting intermediates that were observed by NMR spectroscopy.…”
mentioning
confidence: 99%
See 1 more Smart Citation